High capacity and exceptional cycling stability of ternary metal sulfide nanorods as Li ion battery anodes1. Issue 69 (7th September 2015) - Bhattacharjya, Dhrubajyoti; Sinhamahapatra, Apurba; Ko, Jae-Jung; Yu, Jong-Sung
<x xml:space="preserve">Abstract</x> Ternary spinel NiCo2S4 nanorods demonstrate high specific capacity and outstanding cycling stability as Li ion battery anodes due to restriction of a polymeric gel passivation layer by the CMC–PAA composite binder.